A Roman Portrait’s Metamorphosis: the “Sallust” Bust from the Hermitage Collection - Trofimova, Anna A. (Actual Problems of Theory and History of Art, 2015)
A typical example of ancient Roman portrait that was undergoing changes in course of several centuries is the so-called “Sallust” held by the Hermitage museum. Inscription on a plinth was recognized to be a fraud, while the bust was attributed to Roman work of the period of Trajan’s reign (early 90s AD or early 2nd century AD). Compared with the renowned items from the Trajan epoch, the Hermitage bust was always notable for its unusual style. Detailed study of the piece allowed the author to prove that the ancient original was reworked and styled as a Republican portrait around 125–150 AD. The greater changers touched upon the face: corrections made the original image strikingly different. Traces of the changes made in antiquity evidently differ from the later ones that were added supposedly in the first half of the 19th century when the sculpture was held by G.-P. Campana. Judging from the genuine areas of the surface, the original style of the piece should be referred to as monumental, more simple, rough, and schematic. Its new version is characterized with exaggerated physiognomic sharp features and glance full of fanaticism, which correspond the idea of the Roman historian Sallust. It is thus not surprising that in the 19th century the name was added to a portrayed person to assign a higher price to the piece.
Keywords: ancient Roman portrait; portrait of Sallust; Emperor Trajan; art of Ancient Rome; G.-P. Campana; The State Hermitage Museum; history of restoration; ancient rework of sculpture